Adolescents and adults with autism spectrum disorders - Reichow, Brian; McPartland, James C.; Volkmar, Fred R. (Springer New York, 2014)
The research on children with autism spectrum disorders (ASD) is extensive and growing. Although these conditions are recognized as affecting the entire lifespan, the literature on ASD after childhood is limited and has not been brought together in a single volume in over a decade. Adolescents and Adults with Autism Spectrum Disorders fills this knowledge gap by focusing on needs and difficulties unique to these stages of development. Expert contributors offer cogent reviews of complex issues, from education to employment, leisure activities to illegal behaviors, mental health issues to medical health concerns. The latest findings in key areas, such as psychosocial and residential treatments, social skills programs, epidemiology, the impact of ASD on families, are examined in detail. Throughout the volume, coverage focuses on areas requiring improved models of assessment, updated data, new interventions, and increased support services. Featured topics include: Transition from high school to adulthood for adolescents and young adults with ASD. Innovative programming to support college students with ASD. Romantic relationships, sexuality, and ASD. Treatment of mental health comorbidities. Assessment and treatment planning in adults with ASD. The range of outcomes and challenges in middle and later life. Adolescents and Adults with Autism Spectrum Disorders is a must-have reference for a wide range of clinicians and practitioners - as well as researchers and graduate students - in clinical child, school, and developmental psychology; child and adolescent psychiatry; social work; rehabilitation medicine/therapy; education; and general practice/family medicine.  It will also serve as an important resource for parents and caregivers with its focus on translating the current state of knowledge relevant to understanding adolescents and adults with ASD into practical and relevant recommendations on how best to support them.